Rustificação de mudas de Cordia trichotoma e Tabebuia roseo-alba por jasmonatos e flexões caulinares - Fraga, Danielle Acco Cadorin de (2017)
The submission of seedlings to mechanical and chemical stimuli during the hardening phase in nurseries promotes morphological and physiologies changes that can improve quality attributes and induce better performance in the field. The study aimed to evaluate the effects of applying jasmonates and stem bending in hardening, initial growth and lignification in Cordia trichotoma and Tabebuia roseo-alba seedlings. Cordia trichotoma seedlings were subjected to 20 stem bending daily for 4 weeks and for 8 weeks; 50 μmol L-1 of methyl jasmonate applied weekly for 4 weeks; 50 μmol L-1 of methyl jasmonate applied weekly for 8 weeks and the control treatment. The design was a completely randomized, with five repetitions of the fourteen seedlings. Tabebuia roseo-alba seedlings were subjected to 20 stem bending daily for 4 weeks and for 8 weeks; 1 μmol L-1 of jasmonic acid applied weekly for 4 weeks and for 8 weeks and the control treatment. The design was a randomizes blocks, with five repetitions of the sixteen seedlings. Cordia trichotoma seedlings submitted to hardening treatments showed less increment in height, greater increment in stem diameter and less value for strength index. Seedlings of control treatment had greater loss of root tissue electrolytes and less potential for root regeneration. In the field, 180 days after planting, seedlings submitted to eight weeks of stem bending and eight methyl jasmonate applications showed greater increment in height and stem diameter. In Tabebuia roseo-alba, seedlings treated with jasmonic acid for 8 weeks resulted in higher increment in stem diameter compared to control seedlings. Stem bending for 8 weeks resulted in seedling with fewer leaves and less aboveground dry biomass compared to the other treatments. The results of electrolyte leakage from root tissues of control seedlings showed higher value compared to results from seedlings subjected to either physical or chemical treatments. Total chlrorophyll content was significantly reduced in leaves from seedling submitted to stem bending for 8 weeks and application of jasmonic acid for 4 weeks compared to the control seedlings. After planting in the field, there was no difference in hight and diameter increments between the different treatments. Both species had higher lignin from shoot with appiclations of stem bending for eight weeks and both showed no difference in the lignin concentration of the root tissue. After 360 days of planting in the field for Tabebuia roseo-alba and 450 days for Cordia trichomota, no significant differences were detected in the lignin concentration of shoot tissues.